Report of the Conference (FAO RomeIT, 1992)
Reports on six subjects discussed viz. issues and requirements of small island countries for sustainable development and environment in Agriculture, forestry and fisheries; integrated planning and management; UNCED and the outcome of the Fourth Preparatory Committee; sustainable agriculture and rural development; forest resources management; and coastal fisheries development. Presents the Bridgetown Declaration and lists conclusions and recommendations.
DC